Losing Happily? The Mitigating Effect of Democracy and Quality of Government on the Winner–Loser Gap in Political Support. Issue 9 (28th July 2016) - Dahlberg, Stefan; Linde, Jonas
ABSTRACT: Although a winner–loser gap in political support is present in most democracies, in some countries losers are more content than in others. Earlier research has demonstrated that formal institutional arrangements may affect the size of the gap. In this article, we argue that the quality and performance of institutions are more important than type of institutional arrangements when it comes to the size of the winner–loser gap. A well-functioning democracy on the input-side of the political system and high quality of government on the output-side significantly narrows the gap in support between electoral winners and losers in European democracies.